Effect of Homogenization on Microstructure and Mechanical Property of Mg-5.9Zn-1.6Zr-1.6Nd-0.9Y Alloy. Issue 5 (May 2018) - Liangming, Yan; Yuhao, Liu; Ge, Shi; Jian, Sun; Xiaogang, Li; Huimin, Liu
Abstract: The microstructure evolution of Mg-5.9Zn-1.6Zr-1.6Nd-0.9Y alloy during homogenization was investigated by differential thermal analysis (DSC), optical microscopy (OM), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and X-ray diffraction. Meanwhile, the Viker's hardness (HV) was tested. Results show that the microstructure of as-cast Mg-5.9Zn-1.6Zr-1.6Nd-0.9Y alloy consists of α -Mg, Mg3 (Y, Nd)2 Zn3 (W), Zn-Zr, Mg12 (Y, Nd)Zn (X) and Mg3 (Y, Nd)Zn6 (I) phases?The as-cast sample has an endothermic peak at 510 °C, which disappears in the alloy homogenized at 500 °C for 16 h. A small quantity of W phases dissolve at 470 and 490 °C. However, after homogenization at 500 °C for 16 h, there is only a small number of W, I and X phases, and dendritic segregation is almost eliminated. Therefore, the optimum homogenization parameter is 500 °C for 16 h. Homogenization can effectively decrease the hardness of the as-cast Mg-5.9Zn-1.6Zr-1.6Nd-0.9Y alloy from 1852 MPa to 1442 MPa, so it is beneficial to further deformation of the alloy.